2020
DOI: 10.3390/jcm9030727
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Activity Patterns in Adolescent Patients with Anorexia Nervosa and Their Effect on Weight Gain

Abstract: 1) Background: Altered physical activity (PA) affects weight recovery in anorexia nervosa (AN) patients. The study aimed to objectively characterize PA patterns and their effect on weight trajectory in adolescent AN patients. (2) Methods: PA was assessed in 47 patients on admission to inpatient treatment, in n = 25 of these patients again 4 weeks after discharge (follow-up, FU), as well as in 20 adolescent healthy controls using the Sense Wear™ armband. The following PA categories were defined by metabolic equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Thirty‐three papers were identified that used sensors to measure physical activity levels and energy expenditure (see Table 1). The majority of studies used accelerometers to measure physical activity (Alberti et al, 2013; Belak et al, 2017; Bezzina et al, 2019; Bratland‐Sanda et al, 2011, 2012; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010a; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010b; Bratland‐Sanda, Sundgot‐Borgen, Rosenvinge, et al, 2010; Carrera et al, 2012; Duriez, Guy‐Rubin, et al, 2021; El Ghoch et al, 2013, 2016; Grosser et al, 2020; Hofmann et al, 2017; Holtkamp et al, 2006; Kemmer et al, 2020; Keyes et al, 2015; Klein et al, 2007; Kolar et al, 2020; Lampe et al, 2021; Langlet et al, 2021; Lehmann et al, 2018; Martinez‐Sanchez et al, 2020; Mathisen, Bratland‐Sanda, et al, 2018; Mathisen, Rosenvinge, et al, 2018; McDuffie, 1998; Sauchelli et al, 2015; Stengel et al, 2017; van Elburg et al, 2007; Wons et al, 2021; Zeeck et al, 2020). Other sensors utilized include pedometers (Blinder et al, 1970; Crandall, 2004), multi‐sensor full‐body systems including the Intelligent Device for Energy Expenditure and Activity and the Tracmor physical activity sensor system (Bouten et al, 1996; Gianini et al, 2016; Harris et al, 2008), and indirect calorimeter (Bouten et al, 1996; Harris et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three papers were identified that used sensors to measure physical activity levels and energy expenditure (see Table 1). The majority of studies used accelerometers to measure physical activity (Alberti et al, 2013; Belak et al, 2017; Bezzina et al, 2019; Bratland‐Sanda et al, 2011, 2012; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010a; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010b; Bratland‐Sanda, Sundgot‐Borgen, Rosenvinge, et al, 2010; Carrera et al, 2012; Duriez, Guy‐Rubin, et al, 2021; El Ghoch et al, 2013, 2016; Grosser et al, 2020; Hofmann et al, 2017; Holtkamp et al, 2006; Kemmer et al, 2020; Keyes et al, 2015; Klein et al, 2007; Kolar et al, 2020; Lampe et al, 2021; Langlet et al, 2021; Lehmann et al, 2018; Martinez‐Sanchez et al, 2020; Mathisen, Bratland‐Sanda, et al, 2018; Mathisen, Rosenvinge, et al, 2018; McDuffie, 1998; Sauchelli et al, 2015; Stengel et al, 2017; van Elburg et al, 2007; Wons et al, 2021; Zeeck et al, 2020). Other sensors utilized include pedometers (Blinder et al, 1970; Crandall, 2004), multi‐sensor full‐body systems including the Intelligent Device for Energy Expenditure and Activity and the Tracmor physical activity sensor system (Bouten et al, 1996; Gianini et al, 2016; Harris et al, 2008), and indirect calorimeter (Bouten et al, 1996; Harris et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In one such study, researchers found no significant effect of physical activity on recovery rates [ 21 ]. Meanwhile, a more recent study showed that patients with higher light physical activity at admission had a higher inpatient BMI percentage gain, but a loss of BMI percentage gain at follow-up [ 52 ]. A reason for these discrepancies could be different patient groups or treatments, but also differences in methods (i.e., activity metrics, body placement, devices and proprietary algorithms).…”
Section: Discussionmentioning
confidence: 99%
“…Once spontaneous physical activity levels, conceptualized as "daily physical activity not due to exercise" [59,60] and "all physical activity behavior that emanates from an inherent drive for movement" [61], were recorded in severely underweight AN patients, no differences were found in comparison to spontaneous physical activity levels in healthy normal weight subjects [9,46,62]. For a review of these studies, see [63].…”
Section: Physical Fitness and Physical Activity In Anmentioning
confidence: 99%